Pengaruh Lama Fermentasi terhadap Karakteristik Soyghurt Drink dengan Penambahan Lactobacillus rhamnosus SKG 34 - Putri Dhahana, Karlina Ayu; Nocianitri, Komang Ayu; Duniaji, Agus Slamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
This research aims to find out the effect of fermentation time on the characteristics of soyghurt drink which was fermented by Lactobacillus rhamnosus SKG 34 and to identify the right fermentation time to produce soyghurt drink with the best characteristics. This research uses a Completely Randomized Design (CRD) with time of fermentation as the main factor that consists of 6 levels that are 0, 5 10, 15, 20 and 25 hours. Each treatment was repeated 3 times resulting 18 experimental units. The data were analyzed by analysis of variance (ANOVA) and if the treatment has a significant effect (P<0,05), then proceed with the Duncan Multiple Range Test. The results showed that the fermentation time had a significant effect on total LAB, total acidity, pH, aroma, sweet and sour flavor, overall accaptance, but had no significant effect on total sugar and color of soyghurt drink. The 5 hours fermentation time treatment produced the best characteristics of soyghurt drink, with the following characteristics: total LAB 9.47 log CFU/ ml, total sugar 9.64%, total acid 0.45%, pH 5.17, white color, with slightly sweet and sour taste, slightly liked aroma and liked overall acceptance.